Investigation of early medieval pottery production in Lower Austria: an archaeological science approach - Polyak, T (Cranfield University, 2021)
This thesis aims to contribute to a better understanding of early medieval pottery production in Lower Austria by the scientific analysis of ceramics. The investigation is based on 135 potsherds, including graphite-containing ceramics, which originate from the Erlauf Valley and other sites of Lower Austria and Vienna. The ceramics are dated to the 1st–12th centuries AD, with a majority of samples (n=123) from the 6th–11th centuries AD. The potsherds are studied, in addition to macroscopic analysis, by four scientific methods: petrographic thin section analysis, scanning electron microscopy (SEM), inductively coupled plasma optical emission spectrometry (ICP-OES) and X-ray diffraction (XRD). These methods are used to identify and characterise the origin and manufacturing technology of the ceramics in order to gain insight into wider aspects of pottery production such as the organisation of production, technological choices, traditions and innovation. The compositions of the studied ceramics are consistent with different parts of one geological unit, the Bohemian Massif. This information, together with the distribution of the pots, provides details about connectivity and suggests the presence of local, regional and supra-regional trade/exchange networks within the study area. Traces of the applied production techniques indicate a relatively low level of standardisation for most of the ceramics; observations in this regard along with scale, degree of control and specialisation are used to discuss organisation of production. Through the reconstruction of the ceramic making process, technological choices are examined, such as the use of a new raw material, graphite, from the 8th/9th centuries. The analysis of the manufacturing steps also sheds light on practices of different periods and reveals, for example, differences in raw material preparation between the 1st–7 th and 8th–9 th centuries, which suggest a more sophisticated technology of pottery production in the former than in the latter period in the Erlauf Valley.
Keywords: Ceramic archaeometry; Graphite-containing ceramics; Ceramic petrography; Petrographic thin section analysis